Learning styles of elite and sub-elite athletes - Braakhuis, A. J. (Journal of Human Sport & Exercise, 2015)
Athletes have preferences for the way in which they internalise and process information. Athlete educators, such as coaches and sports medical staff, rarely consider the learning style of an prior to education. This study aims to characterise a range of athletes with regards to their learning style, to increase awareness and conversation about athletes as learners. Athletes (n=93; 44 males, 49 females), age 24 ±8 yrs, completed the VARK (Visual, Aural, Read/write and Kinesthetic) questionnaire and outcomes were analyzed by Chi-Square analysis. Athletes were predominantly K (38%) and MM (33%) in their learning preferences. There was a significant relationship between gender and VARK preference (X2= 15.1, p<0.05), between athletic status and VARK preference (X2=20.4, p<0.05), but little relationship between individual or team sport athlete and VARK preference (X2= 5.3, p=0.16). Very few athletes had a visual learning-style preference (n=1). Those working with athletes should be aware of the preference for MM and K learning-styles and the inadequacy of presenting information visually.